Evaluasi Pelayanan Administrasi Perpajakan Berbasis Digital dalam Meningkatkan Kepatuhan Wajib Pajak UMKM - Raihan A. Hanasi; Revalina Is. Hiola; Chintia Yusuf; Citrawaty Yunus; Pratiwi Pratiwi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to evaluate digital-based tax administration services in improving tax compliance among Micro, Small, and Medium Enterprises (MSMEs), especially in the restaurant sector. The research uses a descriptive qualitative approach conducted at the Maghfira Restaurant in Gorontalo City, MSMEs that consistently fulfill their tax obligations. The data was collected through interviews with business owners and supported by secondary data from books, journals, and previous studies related to digital tax services and taxpayer compliance. These findings show that digital tax administration services, such as e-Filing, e-Billing, and other online tax systems, have provided significant convenience in the tax reporting and payment process. This service increases efficiency, reduces administrative burden, and increases taxpayers' awareness and discipline in fulfilling tax obligations on time. Based on the dimensions of SERVQUAL, the digital tax administration system shows reliability, responsiveness, certainty, empathy, and adequate tangible aspects in supporting taxpayer compliance. However, several obstacles were identified, including limited digital literacy among some MSME actors and internet network disruptions that sometimes hinder access to the online tax system. Therefore, the success of digital tax administration services depends not only on technological advances but also on education, socialization, and ongoing mentoring from tax officers. This study concludes that the digitization of tax administration services plays an important role in increasing the compliance of MSME taxpayers and supporting more effective and transparent tax administration.